Validação e determinação de patulina em suco de maçã utilizando cromatografia líquida acoplada a espectrometria de massa tandem - Silva, Cristiane Rosa da (2021)
Patulin (PAT) is a mycotoxin produced by certain fungal species which is frequently found contaminating apples and derived products, especially juice. Several fungal pathogens, in particular Penicillium species, have been identified as causative agents of diseases in apples. PAT contamination may occur due to reasons as geographic differences, climatic conditions, agricultural practices, cultivars and postharvest environment, which may affect fruit composition. This toxic contaminant is associated with mutagenic, immunosuppressive and neurotoxic effects in humans and animals. In Brazil and in the world effective control of PAT contamination depends on reliable analytical methods. This study developed and validated a technique for the analysis of PAT in samples of industrialized apple juice based on liquid-liquid extraction, using acetonitrile as the extraction solvent. Detection via mass spectrometry was performed after Atmospher Pressure Chemical Ionization (APCI). Mean recoveries of 97.5, 92.49 and 96.92% were reached for 4, 8 and 20 μg/L of PAT, respectively. The mean recovery of the method was 95.64%. The reproducibility of the presented methodology was confirmed when the results of a FAPAS proficiency test, showing a 95.9% recovery, in addition to presenting a good selectivity. The method uncertainty was estimated on three different days for three concentrations 4, 8 and 20 μg / L in replicates of 7 times each concentration, obtaining 0.37%, 6.62%The analyte was monitored with an APCI source in negative ion mode to identify its fragments. The 24 analyzed samples presented PAT levels below the limit of quantification.